Seriously, Norman! - Raschka, Christopher (Scholastic, 2011)
Why are grown-ups so insane? That's the question Leonard, Norman, Anna and Emma (the twins) try to answer with the help of Norman's new tutor, Balthazar Birdsong (who is also fairly nuts).